The Scale Effect of Coarse-Grained Materials by Triaxial Test Simulation - Xiaotao Ai; Guangjin Wang; Xiangyun Kong; Bo Cui; Bin Hu; Hongling Ma (Advances in Civil Engineering)
The scale effect is an unavoidable problem in the laboratory test of coarse-grained materials. By combining the self-developed cellular automaton program with laboratory experiments, a method of simulating the triaxial test of coarse-grained materials was proposed in this paper, and a triaxial test numerical specimen that can characterize the discontinuous, nonuniform, and heterogeneous characteristics of bulk geotechnical materials was established. The parallel grading method was adopted to create six grading curves for numerical simulation based on one in situ grading curve. The failure process and the scale effect on the strength and deformation of coarse-grained materials were analyzed and discussed. The results showed that under the same confining pressure, the peak stress and initial deformation modulus Ei increased with the increase of the maximum particle size dmax, while the degree of shear shrinkage and Poisson’s ration υ decreased. As the confining pressure increased, the scale effect of coarse-grained materials would be magnified. If particle breakage and migration were assumed to be neglected, the internal friction angle φ and dmax would be roughly proportional, the cohesive force c fluctuated with the increase of dmax, and the empirical relations between dmax and c and φ were established, respectively, which provides a reference for estimating the actual shear strength parameters of coarse-grained materials on-site. The research results can provide a way of thinking for the study of the scale effect of coarse-grained materials and also have certain reference significance for inferring the strength parameters of the original-graded coarse-grained materials.